Predicting diurnal and sleep/wake seizure patterns in paediatric patients of different ages. Issue 1 (March 2014) - Ramgopal, Sriram; Powell, Christine; Zarowski, Marcin; Alexopoulos, Andreas V.; Kothare, Sanjeev V.; Loddenkemper, Tobias
<x xml:space="preserve">Abstract</x> Aim. To identify factors that influence diurnal and sleep/wake seizure timing in children undergoing tapered drug withdrawal in an epilepsy monitoring unit. Methods. Medical charts of patients that underwent video‐EEG were reviewed. Seizures were evaluated based on their occurrence in three‐hour time intervals (bins) and between wakefulness and sleep. Patients were classified according to EEG localisation and age: infants (≤3 years), children (3–12 years), and adolescents (>12–21 years). Analysis utilising generalised estimating equations with a negative binomial distribution was performed. Results. A total of 390 patients (188 girls; mean age: 9.2 years; SD: 6.0) had 1, 754 seizures. Generalised seizures (109 patients; 490 seizures) occurred more during wakefulness (p<0.001) and during the day (p<0.001). Modelling revealed a greater occurrence of seizures at night with increasing age (p=0.046). Temporal lobe seizures (62 patients; 271 seizures) occurred overall more frequently during wakefulness (p=0.03). Frontal lobe seizures (41 patients; 184 seizures) occurred more frequently during wakefulness in infants (p<0.05) and more frequently during sleep in adolescents (p<0.0001). Adolescents with frontal lobe seizures were 3.6 times more likely to have seizures during sleep compared to other children (95% CI: 1.8–7.2). Conclusion. These findings are suggestive of changes in circadian rhythmicity that may alter seizure susceptibility in different age groups. The results may assist in prediction of periods of greatest seizure propensity.